A Case of Hailey-Hailey Disease Managed With Oral Magnesium Citrate and High-Dose Vitamin D3. Issue 3 (May 2018) - Gu, Kaien; Silver, Shane
Hailey-Hailey disease, or benign familial pemphigus, is a rare blistering disease originally described in 1939. The disease is due to an autosomal dominant mutation in the ATP2C1 gene on chromosome 3, which encodes for an adenosine triphosphate–dependent calcium pump in the Golgi apparatus whose function is to maintain intercellular calcium homeostasis. Common treatments for Hailey-Hailey disease involve calcineurin inhibitors, topical corticosteroids, topical or systemic antibiotics, topical antifungals, ablative lasers, or botulin toxin. In this case report, we highlight a unique case of Hailey-Hailey disease that was resistant to many conventional therapies and ultimately managed with oral magnesium citrate and high-dose vitamin D3 .